Process optimization of the cabinet drying of mango (Mangifera indica L. c.v. Indian) slices using response surface methodology - Ordoña, Sheila Camille S.
This study aimed to optimize the process parameters of the cabinet drying mango (Mangifera indica L cv. Indian) slices using response surface methodology (RSM). Specifically, the study (1) evaluated the effects of stage of ripeness of Indian mango on the quality of cabinet drying mango slices; and, (2) established and validated the optimized cabinet drying parameters that included, temperature (50-80°C ) and loading capacity (0.1-0.45g/cm2), against the following responses: time (min), color L*, a*, b*, water activity (aw), % moisture content (dry basis), and sensory attributes (appearance, color, aroma, texture, flavor, and overall acceptability) of the cabinet dried mango slices. The appropriate stage of ripeness used throughout the study was Indian mango at 9 days after harvest (80 days after flower induction + 9 days after harvest) with the highest acceptability rating of5.39. The optimum process parameter combination of 50°C and a loading capacity of 0.10 g/cm2, with a desirability index of 0.763, was established for cabinet drying of Indian mango slices. This combination of process parameters resulted in dried Indian mangoes with desirable qualities.Validation of the optimized cabinet drying process parameters (temperature and loading capacity) showed that optimal cabinet dried Indian mango slices fall within their respective % confidence (CI) and % prediction intervals (PI) at p<0.05.